Granulocyte Colony-Stimulating Factor Reduces Fibrosis in a Mouse Model of Chronic Pancreatitis - Lin, Wey-Ran (PLoS One, 2014)
BACKGROUND: Chronic pancreatitis (CP) is a necroinflammatory process resulting in extensive pancreatic fibrosis. Granulocyte colony-stimulating factor (G-CSF), a hematopoietic stem cell mobilizer, has been shown to exert an anti-fibrotic effect partly through the enrichment of bone marrow (BM) cells in fibrotic organ. We aimed to test the effect of G-CSF on fibrosis in a mouse model of CP. METHODS: CP was induced in C57Bl/6J mice by consecutive cerulein injection (50 µg/kg/day, 2 days a week) for 6 weeks. Mice were then treated with G-CSF (200 µg/kg/day, 5 day a week) or normal saline for 1 week, and sacrificed at week 7 or week 9 after first cerulein injection. Pancreatic histology, pancreatic matrix metallopeptidase 9 (MMP-9), MMP-13 and collagen expression were examined. Pancreatic myofibroblasts were isolated and cultured with G-CSF. Collagen, MMP-9 and MMP-13 expression by myofibroblasts was examined. The BM-mismatched mice model was used to examine the change of BM-derived myofibroblasts and non-myofibroblastic BM cells by G-CSF in the pancreas. RESULTS: The pancreatic collagen expression were significantly decreased in the G-CSF-treated group sacrificed at week 9. While collagen produced from myofibroblasts was not affected by G-CSF, the increase of MMP13 expression was observed in vitro. There were no effect of G-CSF in the number of myofibroblasts and BM-derived myofibroblasts. However, the number of non-myofibroblastic BM cells and macrophages were significantly increased in the pancreata of cerulein- and G-CSF-treated mice, suggesting a potential anti-fibrotic role of non-myofibroblastic BM cells and macrophages stimulated by G-CSF. CONCLUSIONS: Our data indicated that G-CSF contributed to the regression of pancreatic fibrosis. The anti-fibrotic effects were possibly through the stimulation of MMP-13 from myofibroblasts, and the enhanced accumulation of non-myofibroblastic BM cells and macrophages in the pancreas.